Contextualising the Neolithic Occupation of Southern Vietnam (Terra Australis 42) - Sarjeant, Carmen (ANU Press, 2014)
Contextualising the neolithic in southern Vietnam is conducted through a comparative study of material culture between An Son and the sites of Bến Ðò, Bình Đa, Cù Lao Rùa, Cái Vạn, Cầu Sắt, Đa Kai, Đình Ông, Lộc Giang, Rạch Lá, Rạch Núi and Suối Linh, all in southern Vietnam.